Creating a financial profile test : factors that impact the financial risk tolerance of individuals and their financial profile classification - Kügler, Florentine Louisa (2023)
The research paper “Creating a financial profile test – factors that impact the financial risk tolerance of individuals and their financial profile classification” was written by Florentine Kügler and examines how to construct a financial profile test based on the concept of financial risk tolerance while considering other significant factors. Previous research has shown that the concept is multidimensional and is significantly affected by sociodemographic variables as well as the level of financial literacy. When assessing financial literacy, it is important to acknowledge that the self-assessment of financial literacy is barely representative of a person's actual level of knowledge. In this paper financial literacy was measured through self-assessment and three test questions on compound interest, inflation, and diversification. Financial risk tolerance was measured through a questionnaire, which assessed several dimensions. This allowed testing the impact of financial literacy and sociodemographic factors on financial risk tolerance. Afterwards, a cluster analysis was applied to characterize the financial profiles. The results showed that gender, income, and age have a significant impact on financial risk tolerance, as opposed to financial literacy and education, which is in strong contrast to existing research. In terms of financial profiling, the analysis found that individuals can be classified into low, medium, and high risk tolerance profiles in combination with income, gender, and age.